Efecto del porcentaje de aluminio en una aleación base zinc sobre la dureza y la fluidez mediante molde en espiral colada en arena - Lopez Abanto, Arnaldo Aldrex. (2016)
In this work has studied the effect of the percentage by weight of aluminum in the range of 2-30%, on the hardness and fluidity of a zinc base alloy (ZA), sand mold casting. Test specimens were used hardness according to ASTM E-140 standard, and test specimens were melt the spiral method according Chneider casted in dry sand mold. From the results obtained it is shown that, as the percentage increases in weight of aluminum in the range of 2 to 20%, hardness increases from 67.20 HB to 109.20 HB respectively, and then decreases to 88.80 HB to 30%. This decrease is due to the aluminum-rich phase Υ is HCP. Fluidity decreases from 165 cm to 2% aluminum up to 25.30 cm to 30% aluminum, because the aluminum film forming aluminum oxide (Al2O3) that increase according to the increase in % aluminum, acting as barriers slowing progress of the liquid alloy. It is concluded that the percentage by weight of aluminum, significantly affect the hardness and fluidity in zinc base alloys (ZA), according to the statistical analysis with 95% confidence